2016
DOI: 10.1002/jhm.2560
|View full text |Cite
|
Sign up to set email alerts
|

From discharge to readmission: Understanding the process from the patient perspective

Abstract: BACKGROUND Patient engagement is critical in delivering high‐quality care. However, literature investigating patient perspectives on readmissions is lacking. OBJECTIVES To understand patients' beliefs and attitudes about 30‐day readmissions and to elucidate areas for improvement aimed at reducing readmissions. DESIGN In person survey. SETTING Academic medical center and affiliated community hospital. PATIENTS Patients with 30‐day readmissions to medicine and cardiology services. MEASUREMENTS Patient readiness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 29 publications
2
77
1
1
Order By: Relevance
“…However, Howard‐Anderson et al. () found that patients’ readiness for discharge did not differ with respect to the presence of someone to help at home after discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Howard‐Anderson et al. () found that patients’ readiness for discharge did not differ with respect to the presence of someone to help at home after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on readiness for discharge have revealed that it affects patient outcomes such as readmission (Greysen et al., ; Nguyen et al., ; Nylor et al., ; Weiss, Yakusheva, & Bobay, ; Weiss et al., ), mortality (Halm et al., ; Lau et al., ) and emergency department (ED) visits (Bobay, Jerofke, Weiss, & Yakusheva, ; Jack et al., ). Readiness for discharge can be influenced by many factors such as age, sex, socioeconomic status, comorbidity and income (Bobay et al., ; Coffey & McCarthy, ; Howard‐Anderson, Busuttil, Lonowski, Vangala, & Afsar‐Manesh, ; Lau et al., ; Schmocker et al., ; Weiss, Costa, Yakusheva, & Bobay, ; Weiss & Piacentine, ; Weiss et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these issues may be managed as an outpatient, thereby decreasing the need for hospital readmission. Patients' perceptions of the hospital discharge process and 30‐day readmission were evaluated in a recent survey . Of interest, only a third of patients knew where to get same‐day care outside of an emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…Median age was 3.1 years, and median length of stay was 2.0 days. The median readability score corresponded to a 10th-grade reading level (interquartile range, [8][9][10][11][12]; range, 1-13). Median PEMAT score was 73% (interquartile range, 64%-82%; range, 45%-100%); 36% of instructions scored below 70%, correlating with suboptimal understandability.…”
mentioning
confidence: 99%